2023
DOI: 10.1038/s41419-022-05528-8
|View full text |Cite
|
Sign up to set email alerts
|

The CDK inhibitor AT7519 inhibits human glioblastoma cell growth by inducing apoptosis, pyroptosis and cell cycle arrest

Abstract: Glioblastoma multiforme (GBM) is the most lethal primary brain tumor with a poor median survival of less than 15 months. However, clinical strategies and effective therapies are limited. Here, we found that the second-generation small molecule multi-CDK inhibitor AT7519 is a potential drug for GBM treatment according to high-throughput screening via the Approved Drug Library and Clinical Compound Library (2718 compounds). We found that AT7519 significantly inhibited the cell viability and proliferation of U87M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Cell cycle control describes the regulatory process of cell growth that is dictated by coordinated interactions of various cyclins and their respective cyclin-dependent kinases (CDKs) [ 18 , 19 ]. Cyclins and CDKs together form various checkpoints that can either usher or inhibit progression of a cell through the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle control describes the regulatory process of cell growth that is dictated by coordinated interactions of various cyclins and their respective cyclin-dependent kinases (CDKs) [ 18 , 19 ]. Cyclins and CDKs together form various checkpoints that can either usher or inhibit progression of a cell through the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle dysregulation is one of the key hallmarks of cancer cells. Numerous chemotherapeutic agents cause cell cycle arrest and promote apoptosis to stop the growth of human glioblastoma and other types of cancer cells ( 34 , 35 ). Furthermore, rapamycin has been shown to induce cell cycle arrest in the G 1 phase and promote apoptosis in several cancer types, including renal cancer cells and glioma cells ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies have shown that certain drugs and small molecular inhibitors can induce pyroptosis in GBM. The GBM cell lines LN-229, U87-MG, and U251 after treatment with galangin [ 28 ], kaempferol [ 29 ], benzimidazoles [ 30 ], 4,5-Dimethoxycanthin-6-one [ 31 ] (new LSD1 inhibitor), and AT7519 [ 32 ] (multi-CDKs inhibitors) can induce obvious pyroptosis, and mouse cell-derived xenograft (CDX) model experiments have also illustrated their anti-tumor role. J.Y.…”
Section: Pyroptosis and Glioblastomamentioning
confidence: 99%